Pelatihan Canva untuk Siswa SMP sebagai Media Pembuatan Materi Presentasi - Nidia Enjelita Saragih; Fitriana Harahap; Robiatul Adawiyah; Fildza Hafazana; Husin Sariangsah (Ekspresi : Publikasi Kegiatan Pengabdian Indonesia, 2024)
This training aims to improve Mardhiyah Middle School students' skills in using Canva as a tool to create interesting and informative presentation material. Canva was chosen because of its easy-to-use interface and various graphic design features that can be accessed online. The Service Team carries out training methods including an introduction to basic Canva features, such as using templates, manipulating text, setting layouts, and integrating graphic elements. In addition, this training will focus on developing students' creativity in designing presentations that are aesthetic and easy to understand, taking into account the principles of effective design. The training material also covers color management strategies, information hierarchy, and techniques for arranging content that suits the target audience. It is hoped that after attending this training, students will be more confident in creating quality presentations, using modern technology to express their ideas and information in a visual and professional way. It is hoped that this can also prepare them to face the demands of competence in the current digital era.